ANALISIS DESKRIPTIF IMPLEMENTASI KEBIJAKAN PROGRAM PENDIDIKAN PADA HOMESCHOOLING & PKBM ANUGRAH BANGSA SEMARANG - Fairuza; Ngurah Ayu Nyoman Murniati; Endang Wuryandini (STKIP Subang, 2023)
The aim of this research was to analyze: (a) homeschooling as an alternative education in some communities, (b) homeschooling education programs facilitated by institutions (c) exploring cultural aspects in homeschooling education, (d) the implementation of government policies in the Non-Formal Education shown as equality procedures for homeschoolers. This research applied qualitative methods with a descriptive analysis approach. The subjects in this research were institutions that housed single homeschooling and community homeschooling called Homeschooling and PKBM Anugrah Bangsa. The research was conducted by following the steps and processes of inductive qualitative research. The research found three main findings; (a) the choice of homeschooling as an alternative education with a single (independent) and community (classical) practice model has reasons, motivations, methods and approaches as well as developing children's talents and interests as well as efforts to build a child's future. (b) a factual model of the implementation of government policies in the implementation of educational programs shown as applied curriculum and procedures for switching to formal schools.